Wall slip of bubbles in foams - WEAIRE, DENIS LAWRENCE (American Institute of Physics, 2006)
We present a computational analysis of the flow of liquid foam along a smooth wall, as encountered in the transport of foams in vessels and pipes. We concentrate on the slip of the bubbles at the wall and present some novel finite element calculations of this motion for the case of fully mobile gas/liquid interfaces. Our two-dimensional simulations provide for the first time the bubble shapes and entire flow field, giving detailed insight into the distribution of stresses and dissipation in the system. In particular, we investigate the relationship between the drag force and the slip velocity of the bubble, which for small slip velocities obeys power laws, as predicted by previous semianalytical treatments.
PUBLISHED
Keywords: Condensed Matter Physics; semianalytical treatments